The importance of role models for sustainable behavior (Ökologisches Wirtschaften - Fachzeitschrift, 2010)
Different theoretical concepts and their empirical application display an agreement on un-sustainable consumption behavior. They suggest important roles for modes of consumer choice that do not follow an optimization calculus. Role models like peers, pioneers or change agents are important in overcoming non-sustainable behavioral routines.